Bibliometric analysis of sustainable rural tourism - Yuqing Geng; Siqiao Zhao; Xiaohan Zhang; Jianyi Li; Yan Yan; Juan Gao (Humanities & Social Sciences Communications)
Abstract Sustainable rural tourism (SRT) balances economic development, environmental management, and cultural preservation in rural areas, making it a hot topic. The research on SRT has evolved and covers a wide range of themes; however, comprehensive studies are limited. This paper conducts a bibliometric analysis of SRT research over the past 25 years (2000–2024) using literature in the Web of Science Core Collection and CiteSpace software for visualization, revealing the current state, evolving hotspots, and future trends in SRT research. The results indicate a significant increase in publication numbers in recent years, with notable collaboration between Asian and European institutions. Besides, SRT encompasses diverse topics with strong interdisciplinary connections; the authoritative research dynamics cover SRT resources, stakeholders’ participation, mechanisms and models, and specific SRT types. Furthermore, there is ongoing interest in the correlations between SRT and rural revitalization, tourist satisfaction, and ecosystem services. Additionally, this paper constructs a comprehensive knowledge framework suggesting that future research will further explore SRT resource utilization and interactions between stakeholders and SRT and enrich theories and methods while focusing more on “sustainable rural tourism.” These findings advance both the study and practice of SRT.